Discrimination of Adzuki Bean (Vigna angularis) Geographical Origin by Targeted and Non-Targeted Metabolite Profiling with Gas Chromatography Time-of-Flight Mass Spectrometry - Kim, Tae Jin (Metabolites, 2020)
As international food trade increases, consumers are becoming increasingly interested in food safety and authenticity, which are linked to geographical origin. Adzuki beans (Vigna angularis) are cultivated worldwide, but there are no tools for accurately discriminating their geographical origin. Thus, our study aims to develop a method for discriminating the geographical origin of adzuki beans through targeted and non-targeted metabolite profiling with gas chromatography time-of-flight mass spectrometry combined with multivariate analysis. Orthogonal partial least squares discriminant analysis showed clear discrimination between adzuki beans cultivated in Korea and China. Non-targeted metabolite profiling showed better separation than targeted profiling. Furthermore, citric acid and malic acid were the most notable metabolites for discriminating adzuki beans cultivated in Korea and China. The geographical discrimination method combining non-targeted metabolite profiling and pareto-scaling showed excellent predictability (Q(2) = 0.812). Therefore, it is a suitable prediction tool for the discrimination of geographical origin and is expected to be applicable to the geographical authentication of adzuki beans.